Ekosistem yang terfragmentasi: Analisis Bronfenbrenner terhadap Hambatan Sistemik Pendidikan Inklusif di Wilayah Lembata - Jielqin Funai; Gabriel Durah Langoday (Jurnal Politik Pemerintahan Dharma Praja, 2026)
Inclusive education in poorest, outermost, and disadvantaged (3T) regions is often reduced to mere compliance with regulatory formalities, neglecting the substantive aspects of equitable pedagogy. This study aims to map and analyze systemic the barriers to the implementation of inclusive education in the Lembata Regency, East Nusa Tenggara. This study employs a qualitative approach using Bronfenbrenner’s Ecological Systems Theory framework. Data were collected over five months through 22 key informants (government officials, educators, parents, and community leaders) using purposive and snowball sampling techniques, supplemented by data triangulation via local policy documents. The findings reveal layered structural breakdowns. At the macrosystem level, bureaucratic inertia and a deficit in inclusion literacy lead to disruptions at the ecosystemic level, manifested as superficial inter agency collaboration and the non functioning of the Disability Service Unit. Geographical isolation has been shown to hinder operational services, trigger emotional exhaustion at the microsystem level, and reinforce social exclusion. These findings underscore that inclusive education requires the enactment of specific instruments at the local level, a structural paradigm shift in local government, and the holistic integration of ecosystem based approaches.